On the solution of a quasilinear differential system with periodic coefficients - Shchegolev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The existence of a partial solution is proved for a quasilinear differential system whose coefficients are representable by a trigonometric series with slowly varying coefficients and frequency. The solution obtained has the same structure.